The influence of interface products on the mechanical and electrical properties of graphene aluminum composites - Luo, Youming; Huang, Yaling; Wang, Wendan; Yu, Shaonan; Quanfang, Chen (Surfaces and interfaces, 2024)
Graphene has been identified as an efficient filler to increase the strength and conductivity of aluminum but the reaction between aluminum and graphene at elevated temperature is inevitable. In this research, diverse interfacial products between aluminum and graphene were generated by modulating the sintering temperature, and their influences on the mechanical and electrical characteristics of graphene-aluminum composites were examined. Copper encapsulation on graphene has been utilized to isolate graphene from contacting aluminum directly as well as to doping graphene for conduction purposes. The synthesis of copper-coated graphene-reinforced aluminum composites involved several steps, including electrochemical exfoliation, electroless chemical deposition, mechanical ball milling, and high-pressure sintering. The results demonstrate that the formation of a solid solution between copper nanoparticles and aluminum promotes strong interfacial bonding with graphene, leading to a 22.76 % improvement in the conductivity of the composite compared to the pristine aluminum matrix. Additionally, by minimizing the formation of aluminum carbide, the addition of graphene results in a tensile strength of 404 MPa for the composite material, representing a significant 88.8 % increase over the aluminum matrix. [Display omitted]